Copigmentation of Anthocyanin Extract from Parijoto Fruit (Medinilla speciosa) and Its Stability at Different Temperatures and Heating Durations - Rizki Bhakti Pertiwi; Umar Hafidz Asy'ari Hasbullah; Arief Rakhman Affandi (Indonesian Food and Nutrition Progress, 2021)
Parijoto fruit (Medinilla speciosa) has a red color and contains anthocyanins. Anthocyanins have low stability due to the effect of heating. Copigmentation can be applied to improve the stability of anthocyanins. This research aims to study the effect of the anthocyanin extract from parijoto fruit ratio and copigment on anthocyanin concentration and color stability during heating at different temperatures and durations. Anthocyanin copigmentation using tannic acid in a ratio of 1:20 and 1:40 with control without copigmentation (1:0) showed that increasing the tannic acid copigment would increase anthocyanin concentrations and reduce anthocyanin losses due to increased temperature and heating time. The use of 1:40 tannic acid copigment increased anthocyanin concentration by 38%. In addition, increasing the concentration of tannic acid increased the ability of anthocyanins to maintain color retention during heating and increased temperatures. The use of tannic acid at a ratio of 1:40 only decreased color retention by 16%, compared to control (54%) after heating at 75ºC heating for 120 minutes. Copigmentation with tannic acid up to a ratio of 1:40 was able to maintain the stability of the lightness (L*), the reddish value (a*), and the yellowish value (b*) of the anthocyanins. This study showed that this system is potential for food coloring application in the food industry.